2019
DOI: 10.3390/ijms20184357
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Prevents NOX- and SGLT2-Dependent Oxidative Stress in Lens Cells Exposed to Fructose-Induced Diabetes Mellitus

Abstract: Purpose: Cataracts in patients with diabetes mellitus (DM) are a major cause of blindness in developed and developing countries. This study aims to examine whether the generation of reactive oxygen species (ROS) via the increased expression of glucose transporters (GLUTs) and the receptor for advanced glycation end products (RAGE) influences the cataract development in DM. Methods: Lens epithelial cells (LECs) were isolated during cataract surgery from patients without DM or with DM, but without diabetic retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…NOX4derived ROS play an important role in p38 MAPK signalling [27] and regulation of mitochondrial function [28]. A recent study reports that dapagliflozin decreases NOX4 levels in the LECs from fructose-fed rats, thereby reducing ROS generation during fructoseinduced diabetic cataracts [29]. We confirmed that miR-182-5p inhibited H 2 O 2 -stimulated apoptosis of HLE-B3 cells; however, this effect was reversed by overexpression of NOX4.…”
Section: Discussionsupporting
confidence: 73%
“…NOX4derived ROS play an important role in p38 MAPK signalling [27] and regulation of mitochondrial function [28]. A recent study reports that dapagliflozin decreases NOX4 levels in the LECs from fructose-fed rats, thereby reducing ROS generation during fructoseinduced diabetic cataracts [29]. We confirmed that miR-182-5p inhibited H 2 O 2 -stimulated apoptosis of HLE-B3 cells; however, this effect was reversed by overexpression of NOX4.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, AKR1B1 and RAGE levels were only significantly elevated in the LECs of DM (+) patients in the present study ( Figure 2). Our previous work similarly demonstrated that sodium-dependent glucose cotransporter 2 (SGLT2) inhibitors enabled glycemic control in type 2 diabetes mellitus (T2DM) patients, by downregulating RAGE-induced NADPH oxidase expression in LECs via the inactivation of GLUTs and reduced ROS generation [9]. Wang S. et al reported that AMPKα2 deletion enhanced NADPH oxidase subunit expression and increased oxidative stress in vascular endothelial cells [36].…”
Section: Discussionmentioning
confidence: 94%
“…Superoxide dismutase (SOD) is a predominant antioxidant enzyme in the lens that degrades superoxide radicals (O 2− ) into H 2 O 2 and oxygen. SOD also protects the lens against cataract development in DM models [8,9]. As a consequence, decreased activity of antioxidant enzymes and reducing substances, excessive AR activation, and AGE accumulation are risk factors for DC occurrence [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies using immortalized human tubular epithelial cells (e.g., HK2 cell line) [25][26][27][28], murine tubular epithelial cells [29] or non-renal cells [30,31] investigated either the effects of empa-or of dapagliflozin. Some of them have shown that SGLT2 inhibition reduced the release of inflammatory or fibrotic factors induced by high glucose levels [25][26][27], others found effects on oxidative stress responses [26,30,31]. Our current study looked at whether high glucose induced changes were influenced by either of the two gliflozins.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we found no effect on cell viability, proliferation, and cytotoxicity, a significant reduction in the oxidative stress was found after incubation with dapagliflozin. Chen and co-workers also demonstrated decreased reactive oxidative species after incubation with dapagliflozin in a fructose-induced diabetic milieu [31]. Others investigated the subcellular mechanisms underlying the protective effects of empagliflozin from high glucose-mediated injuries on HK-2 cells [26].…”
Section: Discussionmentioning
confidence: 99%